A Rare Case of Renal Gastrinoma. (2009) - Katkoori, Devendar; Samavedi, Srinivas; Jorda, Merce; Block, Norman L .; Manoharan, Murugesan
Abstract : We present a rare case of renal gastrinoma. To the best of our knowledge, only one case of renal gastrinoma has been reported in the literature so far. An African American male was diagnosed with Zollinger Ellison syndrome at the age of 15 years, when he underwent surgery for peritonitis secondary to duodenal ulcer perforation. Further evaluation was deferred and proton pump inhibitors were prescribed. Later evaluation showed a left renal mass. Serum gastrin levels were 4, 307 pg/ml. A CAT scan of the abdomen showed 4- x 4-cm heterogeneous solid mass in the interpolar region of the left kidney with central hypodensity. Somatostatin scintigraphy confirmed a receptor-positive mass in the same location. Nephrectomy was done and the tumor was diagnosed on histopathological examination as a gastrinoma. At 6-month follow-up, gastrin levels were 72 pg/ml. After a follow-up of 6 years, the patient has no recurrent symptoms.